A principles-based community health center for addressing refugee health: the New Canadians Health Centre - Haight, Jessica; Kruth, Madeleine; Gokiert, Rebecca; Botwe, Augustine; Dzunic-Wachilonga, Anja; Neves, Cristian; Velasquez, Astrid; Whalen-Browne, Molly; Ladha, Tehseen; Rogers, Corinne (Frontiers in Public Health, 2024)
The provision of timely and comprehensive healthcare is a fundamental aspect of resettlement for refugees, who often experience critical unmet health needs. In Canada, this includes connecting refugees with primary care providers to treat acute health conditions, as well as to provide longitudinal and preventative care. However, refugee access to healthcare is often complicated by numerous barriers, such as difficulty navigating health services, financial constraints, language barriers, discrimination, and limited access to physicians. Due to these unmet health needs and barriers to access, there has been a need for dedicated primary healthcare models for refugees that provide integrated and culturally safe care. In response, a refugee community health center, the New Canadians Health Centre (NCHC), was established in Edmonton, Alberta, Canada in 2021. The NCHC operates through an innovative, principles-based model that delivers interdisciplinary primary healthcare services to refugees that are culturally safe, include clients as partners in their care, and are grounded in principles of social justice, equity, and inclusion. Early and effective healthcare services are needed to address the health of refugees; however, there is a lack of research on the development and implementation of dedicated refugee health service models. This paper addresses this gap by providing an in-depth account of the opening of the NCHC as a principles-based community health center for refugees, including the process by which it was established in response to local needs and the development of its principles-based model for supporting refugee health. This community case description will support the development and implementation of other dedicated models for refugee health, and comes at a critical time in which there are rapidly growing refugee populations in Canada and internationally.